Women Icons from North East India - Rashmi, Neeraja (THE PRIMARY TEACHER, 2017)
Surrounded by the eastern Himalayan ranges, North East India comprises the States of Arunachal Pradesh, Assam, Manipur, Meghalaya, Mizoram, Nagaland, Tripura and Sikkim. The region is distinguished by its uneven terrain, multiplicity of ethnic communities and a rich cultural heritage. There is a high concentration of tribal population in the States of Mizoram, Nagaland, Meghalaya, Arunachal Pradesh and Sikkim, and also in some of the hilly districts of Manipur, Assam and Tripura. But due to its location and terrain, the region has for long remained isolated from the rest of the country. So, not much is known about the valour and achievements of women from the area, who have been the harbingers of social change. This article gives a glimpse of the contributions made by some of these women icons in various walks of life as varied as Freedom Struggle, sports and arts.